ANALISIS KARAKTERISTIK PENGGUNA MODA TRANSPORTASI ONLINE DAN TRANSPORTASI KONVENSIONAL DI KOTA DENPASAR (Contoh Kasus: Go-Car dan Sarbagita) - Rosnyati Cartona; Ni Ketut Sri Astati Sukawati; Cokorda Putra Wirasutama (Jurnal Ilmiah Teknik Universitas Mahasaraswati Denpasar (JITUMAS), 2021)
The selection of transportation modes in Denpasar aims to identify the characteristics of users ofonline transportation modes (Go-Car) and conventional transportation (Sarbagita). Conventional transportationsarbagita also conduct transaction systems without the use of information technology systems, Over time the publicconsiders that the use of transportation must be adjusted to the main needs such as coefficients of time and distanceso that the purpose of the use of transportation can support the needs of the community that must be created bythe coefficient of time and fares in accordance with the distance traveled such as online transportation modes. Thequestionnaire in this study in the form of google form was then distributed through online media to respondentsand processed using multiple linear regression analysis approach with the help of SPSS V25 program. The resultsof the study of 100 respondents there were 94 respondents who chose the online transportation mode (Go-Car)and 6 respondents who chose conventional mode of transportation (Sarbagita). From the analysis of data showsthat the age of users of online transportation modes (Go-Car) and conventional transportation (Sarbagita) inDenpasar city is 16-55 years, the gender of users of online transportation modes (Go-Car) and conventionaltransportation (Sarbagita) in Denpasar city is 44% who are men and 56% are women, users of onlinetransportation modes (Go-Car) and conventional transportation (Sarbagita) based on the last level of junior highschool as much as 1% , SMA as much as 55%, and S1 as much as 44%, users of online transportation modes oftransportation (Go-Car) and conventional transportation (Sarbagita) based on work consists of Students 7%,Students 28%, Private 49%, Self-employed 1%, Housewives 8%, and civil servants 7%.Keywords: Characteristics,SPSS V25, Multiple Linear Regression.